Water in the Jordan basin. A key element of the peace process and future cooperation in the region - Nerini M. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The Peace Process has laid the foundations for the mutual recognition of the needs and rights of all basin States, the water problem being part both of the bilateral and the multilateral tracks of negotiations. The attainment of a lasting peace among riparians will require an equitable arrangement on redistribution of existing water resources, but will not automatically provide a solution to the ever-increasing water scarcity affecting the whole Jordan basin area. The appropriate approach to the water problem consists of a combination of diplomatic efforts by the Parties to re-define their respective water rights and quotas, together with forms of technical cooperation aimed at increasing the overall water potential of the basin, possibly through the development of transboundary projects. The role and potential support from the International Community.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)